Diabetes in pregnancy and offspring cardiac function: a systematic review and meta-analysis - Skovsgaard, Camilla Bjørn; Møller, Anna; Bjerre, Jesper Vandborg; Kampmann, Ulla; Kyng, Kasper Jacobsen (Frontiers in Pediatrics, 2024)
Introduction: Diabetes in pregnancy is associated with impaired offspring cardiac function. The objective of this systematic review was to determine the effect of diabetes in pregnancy on cardiac function in the offspring measured by echocardiography.Methods: PubMed, Embase, Cochrane CENTRAL and Web of Science databases were searched from 1992 to June 27, 2023. Studies reporting offspring (age < 18 years) cardiac function by echocardiography compared between any type of diabetes in pregnancy and healthy control pregnancies were included. Study selection, quality assessment and risk of bias was independently performed by two reviewers. Meta-analyses was performed where possible.Results: Thirty-one observational studies were included 1679 cases and 2694 controls. In the first week of life (23 studies, n=2663), intraventricular septum diastolic diameter (hypertrophy) was increased, while myocardial performance index (global function) and LV E/A-ratio (diastolic function) were decreased. No difference was found for left ventricular ejection fraction (systolic function). At 1-6 months (4 studies, n=454) studies found hypertrophy, and decreased global function, but no difference in systolic or diastolic function. At 1-8 years (7 studies, n=1609) no difference was found. The available data did not allow for sub-analysis based on the type of diabetes, treatment, or glycemic control.Diabetes in pregnancy is associated with cardiac hypertrophy and impaired global cardiac function in infants up to six months old. The few studies reporting on older children found no difference in the parameters investigated. Longitudinal studies employing more advanced echocardiographic measures or MRI are needed to evaluate consequences for long-term cardiac health.